Infiltrative Therapy of Adipose Vital Micrografts in a Metabolic and protective Solution in Peyronie's Disease: a Case Report in a Pilot Study - Svolacchia, Lorenzo; Svolacchia, Fabiano; Maurisi, Angela (Scripta Medica, 2026)
Peyronie's disease (PD) or induratio penis plastica (IPP), is characterised by fibrotic plaque formation within the tunica albuginea, leading to penile curvature and pain. Current minimally invasive treatments provide limited outcomes. Aim of the research was to explore the preliminary feasibility and tolerability of intralesional injections of viable adipose-derived micrografts composed of mesenchymal stem cells (MSCs) and their exosomes, emulsified with a metabolic and protective solution of non-cross-linked hyaluronic acid, amino acid chains and sodium bicarbonate. A 52-year-old male presented with a 12-month history of penile curvature and painful erections. He underwent a single injection of adipose-derived micrografts (20-40 microns) composed of mesenchymal stem cells (MSCs) and their exosomes and emulsified with a metabolic and protective solution of non-cross-linked hyaluronic acid, amino acids branches and sodium bicarbonate for pH stabilisation directly into the plaque. Outcomes were assessed at baseline and 6 months post-treatment using goniometry, Visual Analogue Scale (VAS) for pain and International Index of Erectile Function-5 (IIEF-5). At 6 months, penile curvature decreased from 28° to 22°, a 21 % reduction. Pain resolved completely (VAS from 5 to 0) and erectile function improved (IIEF-5 from 17 to 21). No adverse events were reported. This single case report provides preliminary, hypothesis-generating observations suggesting that intralesional injection of adipose-derived micrografts combined with a metabolic and protective hyaluronic acid solution is feasible and apparently well tolerated in one patient with Peyronie’s disease. The observed numerical improvements in curvature, pain and erectile function cannot be attributed to the treatment with confidence in the absence of a control group and may reflect the natural history of the disease. This approach was investigational and not currently endorsed by EAU or AUA guidelines. Larger randomised controlled studies are required before any conclusion on efficacy can be drawn.
Keywords: Mesenchymal stem cells, adipose-derived; Stem cells; Adipose tissue; Penile induration; Exosomes